Electoral Discrimination: The Relationship between Skin Color and Vote Buying in Latin America. (13th November 2019) - Johnson, Marcus
Abstract: Under what conditions do elections produce racially discriminatory outcomes? This article proposes electoral discrimination as an electoral mechanism for racial marginalization in indigenous and Afro-descendant Latin America. Electoral discrimination occurs when voters are mobilized under differential terms of electoral inclusion based on their observable characteristics. Using the 2010–2014 rounds of the AmericasBarometer and a conjoint experiment, the author finds that skin color is a robust predictor of vote buying across countries in the region with large, visible black and indigenous populations. A significant portion of the relationship between skin color and vote buying is due to the disproportionate impacts of race-neutral targeting criteria on dark-skinned voters. Observed differences in wealth, political and civic engagement, partisanship, political interest, interpersonal trust, and geography together explain a portion of the skin color–client gap, although the individual contribution of each of these factors differs by country. In addition, the author finds an independent relationship between skin color and vote buying over and above these race-neutral factors. The argument and findings in this article speak broadly to the consequences of electoral mobilization in ethnoracially stratified states in Latin America and beyond.